Economic evaluation of the direct use values of goods and services provided by the Bagré wetland in Burkina Faso - Aicha Tapsoba (European Scientific Journal, ESJ, 2024)
Aim missing this study examines the sustainability of the Bagré wetland in Burkina Faso by assessing the direct use values ​​of its ecosystem goods and services. It is accompanied by practical policy recommendations and aims to contribute to strengthening the country's economic growth. The conceptual framework of Munasinghe's (1992) theory and the economic evaluation guide developed by Somda and Awaïs (2013) made it possible to identify and evaluate the direct use values ​​in the Bagré wetland. A documentary synthesis and individual surveys with a sample of 120 stakeholders spread across nine municipalities were carried out. The summary identifies agricultural, fishing, and forestry resources as the zone's main direct-use goods. Data analysis shows that the monetary value of agricultural and fishery production from 1989 to 2019 is 141,251,106,000 FCFA, distributed into nearly 41% for rice and 29% for fish products. The areas sown during this period cover 89,967 ha. Forestry potential is estimated at around 19 billion FCFA, distributed into 54% for non-timber forest products and 44% for firewood. The direct use value of the Bagré wetland in three decades is estimated at over 160 billion FCFA. The challenges of promoting direct-use goods affect the country's gross domestic product, food self-sufficiency, and job creation. Also, irrational valorization actions negatively impact ecosystems and degrade natural resources. Political implications must be considered for sustainable and inclusive management.